Evaluation and Treatment of Cadmium Present in the Industrial Wastewater of the North Refineries Company by Using Attapulgite-NiCoFe2O4 - Saleh, Muafaq Anhab (Journal for Research in Applied Sciences and Biotechnology, 2023)
In this study, a nanomaterial is synthesized from attapulgite clay to act as a new adsorption material. The synthesis of (Attapulgite-NiCoFe2O4) is demonstrated within nanoscale measurements using X-ray Diffraction (XRD) measurements, Scanning Electron Microscopy (SEM), Vibrating Sample Magnetometry (VSM) Analysis, and Transmission Electron Microscopy (TEM). Batch operations are carried out to study the effect of acidity, contact time, adsorbent dose, and ion concentration. The prepared material (altapnlgite-NiCoFe2O4) has achieved high efficiency in removing cadmium metal at the optimum pH (7), at its optimal dose (250 mg/L) and the concentration of the adsorbent (the prepared ion solution) (0.023 mg/L) with the contact time (30 min). The removal rate of cadmium is 92% under the influence of these conditions.